2005
DOI: 10.1590/s1516-89132005000500009
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to the air exposition test of Hoplias lacerdae larvae and juvenile during its initial development

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
12
0
4
Order By: Relevance
“…However, before being submitted to the air exposure test, these two fresh water species were fed live food during the larviculture phase, suggesting the importance of food during this initial phase. For Hoplias lacerdae larvae and fingerlings, when exposed to air on drying paper, Luz & Portella (2005) observed that times similar to those for tilapia could be used; they were between 7 and 10 minutes. However, according to these authors, air exposure on drying paper is a more stressful method, due to the fact that the animals dry up.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, before being submitted to the air exposure test, these two fresh water species were fed live food during the larviculture phase, suggesting the importance of food during this initial phase. For Hoplias lacerdae larvae and fingerlings, when exposed to air on drying paper, Luz & Portella (2005) observed that times similar to those for tilapia could be used; they were between 7 and 10 minutes. However, according to these authors, air exposure on drying paper is a more stressful method, due to the fact that the animals dry up.…”
Section: Resultsmentioning
confidence: 96%
“…Resistance to stress tests may, along with these variables, be a support tool to evaluate the quality of larvae and fingerlings production (Dhert et al, 1992). Amongst the stress tests, air exposure is usually used for several species (Sakakura et al, 1998;Arends et al, 1999;Benfey & Biron, 2000;Martins et al, 2000;Koven et al, 2001;Van Anholt et al, 2004;Luz & Portella, 2005;Luz, 2007;Trushenski et al, 2010), and it is efficient for the evaluation of food quality on the stress resistance rate (Ako et al, 1994;Kanazawa, 1997;Luz, 2007). These tests may point to the effects of diet on the improvement of the health of the animals (Ako et al, 1994) and indicate the lot quality through the relationship between stress resistance, growth and survival results (Luz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These authors also observed that salmonids (the most sensitive group) maintained in saltwater were more sensitive to petroleum than those tested in freshwater, demonstrating that salinity also has an important effect. Several studies (Rantin et al, 1993;Luz and Portella, 2005) have reported that erythrinids, especially H. aff. malabaricus, have a high degree of resistance to environmental conditions involving hypoxia, long-term feeding deprivation and temperature extremes (Rantin et al, 1992;Rios et al, 2002;Rios et al, 2004;Petry et al, 2007), which negatively affect most of the sympatric fish species (Soares et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of larvae to air for a predetermined period of time is a commonly used stress test (benFey and biron, 2000;Martins et al, 2000;koVen et al, 2001; Van anholt et al, 2004, luz andPortella, 2005;luz, 2007) and is effective in assessing the effect of food quality on the rate of stress resistance (ako et al, 1994;kanazaWa, 1997;luz, 2007;luz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%